Agglomeration, Integration, and Territorial Authority Scale in a System of Trading Cities. Centralisation versus Devolution - Massimo Del Gatto (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper emphasises the importance of the political-institutional dimension in the understanding of the spatial distribution of economic activity. We introduce the notion of Territorial Authority Scale, which refers to the degree of devolution (towards sub-national tiers of government) involved in the authority to decide on Spatial Policy, and propose a model of 'agglomeration in a system of cities' in which both intra-city trade and inter-city trade are considered. Enriching both the literature on integration/agglomeration and that on city size and formation, we show that: i) devolution results in over-agglomeration (fewer cities, which tend to be over-sized) and low welfare; ii) the higher the level of spatial (i.e. transport costs) and economic (i.e. intensity of trade) integration, the higher is the magnitude of the inefficiency. From a theoretical point of view, the paper represents an attempt to import, into geographical economics, a 'scale approach', which is an established approach to the notion of space in sociology.
Keywords: F12; F15; L11; L13; R12; R13; R59; 330; Agglomeration; Integration; Cities; Devolution; Economic geography; Transport costs; Spatial policy; Trade; Product variety; Linkages; Regionales Cluster; Stadtökonomik; Agglomerationseffekt; Wirtschaftsgeographie; Transportkosten